Artificial Intelligence as an Epistemological Challenge in Contemporary Islamic Education - Rodianto Rodianto; Abidul Haq; Irfan Haris; Alimatus Sholikhah (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The rapid advancement of Artificial Intelligence (AI) has significantly transformed educational practices by reshaping how knowledge is produced, mediated, and legitimized. In Islamic education, where epistemology is grounded in the integration of revelation, reason, and ethical values, AI introduces challenges that extend beyond technological adoption to the philosophical foundations of knowledge. This study aims to examine AI as an epistemological challenge and formulate a reflective framework for its ethical integration into Islamic education. Employing a qualitative library research approach, the study analyzes recent Scopus- and SINTA-indexed publications alongside primary works on Islamic educational epistemology. The findings indicate that AI may shift educational orientation from meaningful knowledge to instrumental information, weaken teachers’ epistemic authority, and diminish the roles of sanad and adab in knowledge transmission. As its principal contribution, this study proposes a Reflective Epistemological Framework integrating revelation-based knowledge, ethical use of reason and AI, teacher authority, preservation of sanad and adab, and AI literacy with moral responsibility. The study concludes that AI should function as a pedagogical assistant rather than an autonomous epistemic authority, ensuring that technological innovation reinforces the philosophical, ethical, and spiritual foundations of Islamic education.